'Stepping into Other Peoples' Shoes': Teaching and Assessing Empathy in the Secondary History Curriculum. Issue 2 (1st July 2004) - Harris, Richard
The concept of empathy has re-appeared in professional discourse about history teaching. The authors offer a conceptual analysis of this problematic concept, re-visit the objections raised in the 1980s and 90s and conclude that it is a valuable aim for history teaching today. Problems and objections to teaching and assessing empathy are discussed and principles to guide practice are suggested.